Illocutionary Acts in English Teacher-Student Classroom Interaction at Local High School - Kristiwi Rewai; Rusdiana Junaid (Pusat Studi Bahasa dan Publikasi Ilmiah, 2021)
The research aimed at finding out the type of illocutionary acts on interaction between teacher and students in the classroom. The data of this research were the English utterances performed by the English teacher at local high school in Palopo. The teaching and learning process in the class was recorded using a video camera and transcribed. Then, the transcribed dialogues were arranged into the data sheet. Finally, the data were classified according to Searle’s classification of illocutionary acts (1976). The results of the research show that there are four types of illocutionary performed by the English teacher in classroom communication. They are representatives, expressives, directives, and commissives. The directives are the most frequent acts, while the commissives are the fewest frequent acts. Furthermore, there are 18 types of illocutionary functions used by the English teacher, which include stating a fact, informing, explaining, agreeing, greeting, thanking, complimenting, joking, apologizing, commanding, requesting, suggesting, forbidding, questioning, permitting, encouraging, and threatening. Questioning is the most frequent function, while threatening is the fewest frequent function. To sum up, the dominant use of directive acts implies that the teacher dominates the conversation. Meanwhile, the purpose of the use of questioning is to activate students’ background knowledge and critical thinking.